Ethical Considerations during the Informed Consent Process for Acute Ischemic Stroke in International Clinical Trials. Issue 4 (8th July 2022) - Bellomo, Tiffany; Fokas, Jennifer; Tsao, Noah; Anderson, Clare; Becker, Christopher; Gioscia‐Ryan, Rachel; Meurer, William
ABSTRACT: We sought to investigate the experiences of researchers in existing active‐control trials in acute ischemic stroke comparing investigational therapy to tissue plasminogen activator (tPA) in order to identify the approaches and challenges in obtaining informed consent. Out of 401 articles evaluated, 14 trials met inclusion criteria. Trial representatives were contacted to complete a survey concerning the consent process. None of the 14 trials published materials related to the informed consent process. Trials with 75% to 100% of patients directly consented had shorter door‐to‐treatment (DTT) times than trials that directly consented less than 50% of patients. Trials that had translators available (for recruiting participants who were not native speakers in the local language) and translated consent documents had longer DTT times. The study findings suggest that differences in the standards of informed consent internationally may allow more patients with moderate strokes to provide direct consent without delaying DTT time. Future trials should emphasize transparency to the public and scientific community in the informed consent process.